Human resource management : current trends future directions - Bindhu D; Chetana, K M; Anusha T; Basil, Hans V (Ghaziabad P&P Academy, 2025)
The evolution human resource management; remote work; supporting employees mental and physical wellbeing in remote work; wellness Programmers; creating a supportive work Environment; Ethical and sustainable HRM Practices
Keywords: Manangement